Rút gon biểu thức sau
a) \(\left(x-5\right)\left(2x+3\right)+2x\left(1-x\right)\)
b) \(\left(3x-5\right)^2-\left(x+5\right)\left(5-x\right)-\frac{5}{2}\left(-2x\right)^2\)
c) \(\left(3x+2\right)\left(4-6x+9x^2\right)-3x\left(3x-2\right)^2+12\left(-\frac{2}{3}-3x^2\right)\)
a) ( x - 5 )( 2x + 3 ) + 2x( 1 - x )
= 2x2 - 7x - 15 + 2x - 2x2
= -5x - 15
= -5( x + 3 )
b) ( 3x - 5 )2 - ( x + 5 )( 5 - x ) - 5/2( -2x )2
= 9x2 - 30x + 25 + ( x + 5 )( x - 5 ) - 5/2.4x2
= 9x2 - 30x + 25 + x2 - 25 - 10x2
= -30x
c) ( 3x + 2 )( 4 - 6x + 9x2 ) - 3x( 3x - 2 )2 + 12( -2/3 - 3x2 )
= ( 3x )3 + 23 - 3x( 9x2 - 12x + 4 ) - 8 - 36x2
= 27x3 + 8 - 27x3 + 36x2 - 12x - 8 - 36x2
= -12x
a, \(\left(x-5\right)\left(2x+3\right)+2x\left(1-x\right)=2x^2+3x-10x-15+2x-2x^2=-5x-15\)
b, \(\left(3x-5\right)^2-\left(x+5\right)\left(5-x\right)-\frac{5}{2}\left(-2x\right)^2\)
\(=9x^2-30x+25-\left(5x-x^2+25-5x\right)-\frac{5}{2}\left(4x^2\right)\)
\(=-30x\)